Designing asymmetric Dy2 single-molecule magnets with two-step relaxation processes by the modification of the coordination environments of Dy(iii) ions. Issue 26 (19th June 2020) - Huang, Yuan; Li, Jia-Xin; Ge, Yu; Zhang, Xia-Mei; Xu, Yang; Li, Yahong; Zhang, Yi-Quan; Yao, Jin-Lei
Abstract : The reaction of Dy(NO3 )3 ·6H2 O and an asymmetric Schiff-base ligand H2 L afforded two asymmetric dinuclear compound. Both complexes exhibit single-molecule magnet behavior with two-step slow relaxation processes. Abstract : The reaction of Dy(NO3 )3 ·6H2 O and an asymmetric Schiff-base linker 5-chloro-2-(((2-hydroxy-3-methoxybenzyl)imino)methyl) phenol (H2 L) afforded a dinuclear compound [Dy2 L2 (HL)(NO3 )(EtOH)]·0.5C2 H5 OH (1 ). Complex 1 features two inequivalent Dy(iii ) sites, where three ligand sets (one HL − moiety and two L 2− groups) are shared by two Dy(iii ) ions. The strategic introduction of CH3 COOH in the reaction system used for synthesizing 1 induces the replacement of the HL − ligand by the CH3 COO − ion, consequently resulting in the generation of [Et3 NH][Dy2 L2 (NO3 )(CH3 COO)2 ] (2 ). In complex 2, two Dy(iii ) centers adopt NO7 ( D 2d geometry) and NO6 ( C 2v ) coordination sphere, respectively. DC magnetic susceptibility studies for the two complexes indicate ferromagnetic interactions. Complexes 1 and 2 exhibit single-molecule magnet behavior with two-step slow relaxation processes due to the possession of inequivalent metal sites. The energy barriers of 69.19 and 45.73 K for 1, and 92.77 and 72.95 K for 2 are determined. Theoretical calculations reveal that the two-step relaxation processes in both 1 and 2 mainly originate from the single-ion magnetism of two distinct Dy(iii ) ions with inequivalent coordination environments.